The fossil book - Parker, Gary.; Parker, Mary (Mary M.). (Green Forest, AR Master Books, 2005)
Fossils are discussed in the context of Creationism.
Includes bibliographical references (p. 78) and index.
Keywords: Fossils; Paleontology; Creationism